Perubahan Perseroan Terbatas Perorangan Menjadi Perseroan Terbatas Persekutuan Modal Ditinjau Dari Kemanfaatan Hukum - Br Sebayang, Ruhulina; Yenny Yuniawaty Lunandi (UNES Law Review, 2024)
The government provides convenience for Micro and Small Enterprises (hereinafter abbreviated as UMK) by making a breakthrough through Law Number 6 of 2023 concerning the Stipulation of Government Regulations in Lieu of Law Number 2 of 2022 concerning Job Creation into Law. Article 109 of Law Number 6 of 2023 concerning Job Creation reads: "A Limited Liability Company, hereinafter referred to as the Company, is a legal entity that is a capital partnership, established based on an agreement, carrying out business activities with authorized capital entirely divided into shares or individual Legal Entities that meet the criteria for Micro and Small Enterprises as stipulated in the laws and regulations regarding Micro and Small Enterprises." If an individual PT no longer meets the criteria for Micro and Small Enterprises and/or its shareholders become more than 1 person, the Individual PT must change its status to a Capital Partnership as stipulated in Article 17 of the Regulation of the Minister of Law and Human Rights of the Republic of Indonesia Number 21 of 2021 concerning Terms and Procedures for Registration of Establishment, Change and Dissolution of Limited Liability Company Legal Entities. The purpose of this study is to determine and analyze the change of Individual PT to Capital Partnership PT, as well as the legal benefits in changing Individual PT to Capital Partnership PT. This research uses normative juridical methods by taking a statutory approach and a conceptual approach. The nature of the research uses descriptive analysis by reviewing, describing, and explaining legal problems or issues regarding the change of Individual PT to Capital Partnership PT in terms of legal benefits. The results showed that the change of Individual PT to Capital Partnership PT creates legal benefits for Micro and Small Enterprises in the ease of doing business and investing.